Living in Socialism. Comfort and Politics in 1920s Russia - Silvia Rodeschini (Scienza & Politica, 2022)
In 1920s Russia domestic life is the object of a specific political debate that tries to formulate housing forms and comfort models alternative to the one of the bourgeois house. By analysing the texts written by Fourier, Engels and Russian functionalist architects and the discourses that accompany USSR housing policies, the article reconstructs the concepts of comfort underlying this debate and their functions.